Memahami Hubungan Orang Ruimba dan Waris-Jenang dalam Konteks Teori Praktek - Adi Prasetijo (Endogami: Jurnal Ilmiah Kajian Antropologi, 2018)
In the past, the relationship between the Orang Rimba and the outside world had to be through intermediaries or middleman commonly referred to as waris-jenang, appointed by the Jambi Sultanate. Eventually this function gradually changes. With the world increasingly open, and intermediary functions also decreasing, they can interact directly with outside communities. By using a theory practice approach by Bourdieu (1977), we can understand that Orang Rimba of Jambi cannot be seen as victims but more than that, they are active social agents to play a role with the capital they have. They play in the social arena that they understand and have experience in. Their relationship with various parties, including corporations, NGOs, and outside communities gives them symbolic power about how they play their identity as a group of indigenous people.